Estimating the social value of specific crop diversity conservation plans: Do Czechs care more about conserving hop, wine or fruit tree varieties? - Nicholas Tyack; Milan Scasny (Charles University in Prague, Institute of Economic Studies (IES), 2020)
We use a discrete choice experiment to elicit the preferences of Czech adults ages 18 to 69 (n=805) for the conservation of wine, hop, and fruit tree varieties. In addition, we also elicit the preferences of a smaller sub-sample consisting solely of respondents from South Moravia (n=463), an agricultural region of the country. Estimating a mixed logit model, we find a strong public preference for fruit tree conservation and derive a mean willingness to pay (WTP) for the conservation of fruit tree varieties of about 280 Kéc. Mean WTP for wine variety conservation was found to be about 130 Kéc, while WTP for conserving hop varieties was estimated at about 80 Kéc. Mean WTP values among respondents from South Moravia for crop conservation programs were found to be between about three and four times higher than for the general Czech population. We further examine the impact of observed preference heterogeneity for several respondent-specific characteristics on WTP for the conservation of the three crops. In total, the Czech adult population was estimated to have an aggregate WTP of at least two billion Kéc for additional fruit tree conservation over next ten years, about one billion Kéc for the conservation of additional wine varieties, and ~580 million Kéc for the conservation of additional hop varieties, and these values increase by 31-112 percent if the estimated benefits for the maximum number of varieties as offered in our design are added), revealing the previously unmeasured social welfare benefits of these activities. The estimated benefits of specific crop conservation are an important contribution to the valuation of these historic Czech resources, as crop varieties conserved now provide not only option and bequest values but may also be more resistant to biotic stresses (such as pests and diseases) as well as expected adverse weather extremes, providing the potential to help adapt Czech agriculture to future shocks.
Keywords: Q18; Q51; Q57; 330; Crop diversity; plant genetic resources for food and agriculture; discrete choice experiments; mixed logit; willingness to pay; consumer preferences